2007
DOI: 10.1016/j.neuroimage.2006.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging of word priming in males with chronic schizophrenia

Abstract: Word-priming studies have suggested that the associative disturbance of schizophrenia may reflect aberrant spread of activation through the lexicon of the brain. To explore this, we examined lexical activation using a semantic word-priming paradigm coupled with functional magnetic resonance imaging (fMRI). We also wanted to determine whether brain activation to this paradigm correlated with relevant clinical symptom measures. In addition to completing clinical symptom measures, twelve chronic patients and twel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 59 publications
7
42
0
Order By: Relevance
“…While the precise functional interpretation of this observation is somewhat unclear, it may reflect a neural basis of risk for developing unusual ideas, perceptions and disorganized language (Grimshawet al, 2010). Previous studies have also reported relationships between abnormal frontal modulation during language processing and clinical symptoms in participants with FHR and SZ (Whyte et al, 2006; Han et al, 2007), (including a relationship between reduced IFG suppression during semantic priming and clinical symptoms in SZ) (Han et al, 2007). The extent of IFG non-suppression during semantic priming could potentially reflect a continuum of risk for SZ, with moderate levels of non-suppression associated with attenuated positive symptoms, and higher levels, with frank psychosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While the precise functional interpretation of this observation is somewhat unclear, it may reflect a neural basis of risk for developing unusual ideas, perceptions and disorganized language (Grimshawet al, 2010). Previous studies have also reported relationships between abnormal frontal modulation during language processing and clinical symptoms in participants with FHR and SZ (Whyte et al, 2006; Han et al, 2007), (including a relationship between reduced IFG suppression during semantic priming and clinical symptoms in SZ) (Han et al, 2007). The extent of IFG non-suppression during semantic priming could potentially reflect a continuum of risk for SZ, with moderate levels of non-suppression associated with attenuated positive symptoms, and higher levels, with frank psychosis.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with altered semantic processing in SZ, fMRI studies of semantic priming in SZ have reported less association-induced suppression in left frontal and temporal regions (Han et al, 2007; Kuperberg et al, 2007), and sometimes even the opposite pattern of modulation, with more activity to semantically associated relative to unrelated pairs (‘association-induced enhancement’) (Kuperberg et al, 2007). These abnormalities were seen even when behavioral semantic priming was normal.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies of semantic priming have focused on the language network that includes left inferior frontal and left temporal regions (Bergerbest et al, 2009;Han et al, 2007;Tivarus et al, 2006;Wig et al, 2009). Current study, however, demonstrated an independent component showing semantic repetition priming-related activation being broader, and consisting of bilateral orbitofrontal, superior parietal and inferior temporal regions.…”
Section: Discussionmentioning
confidence: 99%
“…The late information processing responsible for N400 during semantic priming task in ERP study could be associated with the dysfunction in left inferior frontal gyrus, as suggested by a functional magnetic resonance imaging (fMRI) study (Kubicki et al, 2003). Schizophrenics also showed a differential increase in activation of both left frontal and temporal cortices from high connectivity to low connectivity to unrelated word pairs (Han et al, 2007). In addition, semantic repetition priming effect (Guillaume et al, 2009) observed with the left inferior frontal gyrus (Bergerbest et al, 2009;Wig et al, 2009) has been also reported to be decreased in schizophrenia (Matsuoka et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation